To Catch the Rain - Grafman, Lonny (Open textbook library., 2017)
To Catch the Rain is targeted at makers – DIYers looking for practical solutions to water problems for themselves or their communities. The book also provides an excellent overview of rainwater harvesting for students and teachers in environmental science, sustainable design, international development and engineering.